Flax Biomass Conversion via Controlled Oxidation: Facile Tuning of Physicochemical Properties - Dehabadi, Leila (Bioengineering (Basel), 2020)
The role of chemical modification of pristine linen fiber (LF) on its physicochemical and adsorption properties is reported in this contribution. The surface and textural properties of the pristine LF and its peroxyacetic acid- (PAF) and chlorite-treated (CF) fiber forms were characterized by several complementary methods: spectroscopy (SEM, TEM, FT-IR, and XPS), thermal analysis (DSC and TGA), gas/water adsorption isotherms, and zeta potential (ξ). The results obtained reveal that the surface charge and textural properties (surface area and pore structure) of the LF material was modified upon chemical treatment, as indicated by changes in the biomass composition, morphology, ξ-values, and water/dye uptake properties of the fiber samples. Particularly, the pristine LF sample displays preferential removal efficiency (E(R)) of methylene blue (MB) dye with E(R) ~3-fold greater (E(R)~62%) as compared to the modified materials (CF or PAF; E(R)~21%), due to the role of surface charge of pectins and lignins present in pristine LF. At higher MB concentration, the relative E(R) values for LF (~19%) relative to CF or PAF (~16%) reveal the greater role of micropore adsorption sites due to the contributing effect of the textural porosity observed for the modified flax biomass at these conditions. Similar trends occur for the adsorption of water in the liquid vs. vapour phases. The chemical treatment of LF alters the polarity/charge of the surface functional groups, and pore structure properties of the chemically treated fibers, according to the variable hydration properties. The surface and textural properties of LF are altered upon chemical modification, according to the variable adsorption properties with liquid water (l) vs. water vapor (g) due to the role of surface- vs. pore-sites. This study contributes to an understanding of the structure-adsorption properties for pristine and oxidized flax fiber biomass. The chemical conversion of such biomass yields biomaterials with tunable surface and textural properties, as evidenced by the unique adsorption properties observed for pristine LF and its modified forms (CF and PAF). This study addresses knowledge gaps in the field by contributing insight on the relationship between structure and adsorption properties of such LF biomass in its pristine and chemically modified forms.